2015
DOI: 10.1097/scs.0000000000001879
|View full text |Cite
|
Sign up to set email alerts
|

Aging as the Impact Factor on Septoplasty Success

Abstract: For many surgical procedures, aging is considered as one of the important prognostic factors on success. To date no study in the literature discussed this relationship between aging and the success of septoplasty. At this point, our results showed that septoplasty is a successfully performed procedure in all ages. But, satisfaction of patients is statistically decreasing with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
1
11
1
3
Order By: Relevance
“…We did not see any difference in results between males and females, which is consistent with most other studies [ 3 , 5 , 6 , 8 ] except one [ 7 ] in which females had less improvement. Older patients showed better improvement than younger ones in our study, although other studies have found no differences by age [ 2 6 ]. Two studies [ 3 , 5 ] reported that there was no difference in results between smokers and nonsmokers, as was our finding.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…We did not see any difference in results between males and females, which is consistent with most other studies [ 3 , 5 , 6 , 8 ] except one [ 7 ] in which females had less improvement. Older patients showed better improvement than younger ones in our study, although other studies have found no differences by age [ 2 6 ]. Two studies [ 3 , 5 ] reported that there was no difference in results between smokers and nonsmokers, as was our finding.…”
Section: Discussioncontrasting
confidence: 89%
“…This information may also be useful to patients in helping them decide whether to have nasal surgery as well as to set realistic expectations regarding likely outcomes. Studies have examined age [ 2 6 ], gender [ 3 , 5 – 8 ], smoking habits [ 3 , 5 ], allergy [ 3 , 6 , 9 13 ], prior surgery [ 6 , 8 ], and preoperative obstruction scores [ 3 , 5 , 14 ] as predictive clues to the outcome of nasal surgery. Only a few studies have examined the type and grade of septal deviation [ 5 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serial photographs document postoperative cosmetic concerns and should be followed over the patient's lifetime (►Figs. [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Septoplasty alone is associated with decreased nasal obstructive symptom improvement with advancing age. 22 Objective measurement of nasal airflow has been directly assessed using rhinomanometry over the past 40 years, greatly increasing our understanding of nasal physiology. 23 However, patient symptoms and objective measurement of the degree of nasal obstruction are often discordant.…”
Section: Nasal Airway Obstructionmentioning
confidence: 99%
“…Habesoglu ve ark. [14] da NOSE skorları verilerine göre hastaların yaşlarına bakılmaksızın düzelme olduğunu belirtmişlerdir. Ayrıca septoplasti sonrası GYI indeksini yaşam kalite anketi olarak kullanmış ve GYI indeksinin ameliyat sonrası istatistiksel olarak anlamlı olduğunu bulmuşlardır.…”
Section: İstatistiksel Yöntemunclassified